Fixing Health Systems - Savigny Don De (editor); Kasale Harun (editor); Mbuya Conrad (editor) (In Focus Collection, 2014)
The daunting health challenges now confronting Africa, and the rest of the developing world, have been well publicized. Malaria, HIV/AIDS, tuberculosis, malnutrition, anemia: all devastating epidemics whose effects are multiplied by conditions of poverty. In Tanzania, however, recent experience and research are providing cause for optimism. In 1993, the World Development Report suggested that mortality rates could be significantly reduced if resources were directed more in line with local "burden of disease." The TEHIP program was founded to test this idea. After a decade of research and exper